Cross-protection and cross-neutralization capacity of ancestral and VOC-matched SARS-CoV-2 adenoviral vector-based vaccines - Vinzon, Sabrina Eugenia (2023)
COVID-19 vaccines were originally designed based on the ancestral Spike protein, but immune escape of emergent Variants of Concern (VOC) jeopardized their efficacy, warranting variant-proof vaccines. Here, we used preclinical rodent models to establish the cross-protective and cross-neutralizing capacity of adenoviral-vectored vaccines expressing VOC-matched Spike. CoroVaxG.3-D.FR, matched to Delta Plus Spike, displayed the highest levels of nAb to the matched VOC and mismatched variants. Cross-protection against viral infection in aged K18-hACE2 mice showed dramatic differences among the different vaccines. While Delta-targeted vaccines fully protected mice from a challenge with Gamma, a Gamma-based vaccine offered only partial protection to Delta challenge. Administration of CorovaxG.3-D.FR in a prime/boost regimen showed that a booster was able to increase the neutralizing capacity of the sera against all variants and fully protect aged K18-hACE2 mice against Omicron BA.1, as a BA.1-targeted vaccine did. The neutralizing capacity of the sera diminished in all cases against Omicron BA.2 and BA.5. Altogether, the data demonstrate that a booster with a vaccine based on an antigenically distant variant, such as Delta or BA.1, has the potential to protect from a wider range of SARS-CoV-2 lineages, although careful surveillance of breakthrough infections will help to evaluate combination vaccines targeting antigenically divergent variants yet to emerge.